Rekonstruksi Fungsi Operasional MSDM: Strategi Pengembangan Kapasitas Pendidik Berbasis Keunggulan Kompetitif di Lembaga Pendidikan Islam - Insyiroh; Fariska Septi Maidita; Saiful Hadi (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to reconstruct the implementation of Human Resource Management (HRM) operational functions while formulating adaptive teacher capacity development strategies toward creating a competitive advantage in Islamic educational institutions. The research method used is descriptive qualitative through a literature review approach (library research). The results indicate that human resources in the Islamic educational ecosystem represent a totality of intrinsic modalities that harmonize physical and spiritual dimensions. The actualization of this latent potential is managed through a mechanistic cycle of seven HRM operational functions, including moral-academic-based staffing, development, fair and decent compensation, maintenance, participative integration, discipline modeled after uswah hasanah, and ethical separation. Furthermore, to confront global disruptions, human resource governance is reconstructed into three pillars of competitive advantage strategy: strengthening integrated spiritual-digital-professional competencies, engineering a quality-oriented organizational culture, and internalizing Islamic work ethics based on prophetic traits (shiddiq, amanah, tabligh, fathanah). This synergy transforms the teaching profession from mere mechanical task executors into a form of worship and high-performing intellectual jihad.